2020
DOI: 10.1002/adfm.202008758
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cell Microenvironment Altered by Gold Nanowire Array and Regulation of Partial Epithelial‐Mesenchymal Transition

Abstract: Cell microenvironment is an essential factor in determining cell growth and cell fate. Many studies have been carried out to understand the functions and mechanisms of small molecules or growth factors/cytokines; however, the effects of the physical environment on cells are relatively unknown. Changes in the cell's physical microenvironment affect cell adhesion and modify intracellular signaling controlled by adhesion properties, resulting in altering the cytoskeletal structure and cellular properties. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Our previous studies showed that controlling the cell microenvironment with nanowire arrays influences changes in cell adhesion and alters the expression of paxillin, which is responsible for signal transduction among the protein complexes involved in integrin-mediated focal adhesion . The CME is the local environment around the cell, containing physical and chemical signals that can affect the cell growth and behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that controlling the cell microenvironment with nanowire arrays influences changes in cell adhesion and alters the expression of paxillin, which is responsible for signal transduction among the protein complexes involved in integrin-mediated focal adhesion . The CME is the local environment around the cell, containing physical and chemical signals that can affect the cell growth and behavior.…”
Section: Resultsmentioning
confidence: 99%
“…42 Our previous studies showed that controlling the cell microenvironment with nanowire arrays influences changes in cell adhesion and alters the expression of paxillin, which is responsible for signal transduction among the protein complexes involved in integrin-mediated focal adhesion. 43 The CME is the local environment around the cell, containing physical and chemical signals that can affect the cell growth and behavior. The signals include extracellular matrix for cell adhesion, diverse cytokines, hormones, reactive species, local physical properties of a cell, and external stimulus through mechanical forces that induce alteration of protein expression inside a cell.…”
Section: Morphological Changes Induced Through External Stimuli Of Ma...mentioning
confidence: 99%
“…Biophysical cues such as electrical stimulation, mechanical properties, and surface topography can guide various stem cell differentiation 21,27,30 . Nanowires provide a unique microenvironment for transmitting specific stimulus to cells, in which decode the stimulus into biochemical signals 47 . However, the molecular mechanism of these stimulus on CSCs behavior has not been fully elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…21,27,30 Nanowires provide a unique microenvironment for transmitting specific stimulus to cells, in which decode the stimulus into biochemical signals. 47 However, the molecular mechanism of these stimulus on CSCs behavior has not been fully elucidated. MSCs.…”
Section: Overcome Drug Resistant Of Cscsmentioning
confidence: 99%
“…Kim et al. [ 53 ] constructed a cell microenvironment by a template-based electrodeposition method and changed physical properties such as topography using gold nanowire arrays, which had a density characteristic of 86.17 ​± ​12.47 wire μm −2 (average diameter of nanowire ​= ​77.6 ​± ​5.2 ​nm; average length of nanowire ​= ​595 ​± ​161 ​nm). The Takai team [ 54 , 55 ] performed the investigation of microgroove-based structures of specific geometrical parameters with different angels (60–120°).…”
Section: Biomaterials Applied In the Artificial Ecm With Key Biophysi...mentioning
confidence: 99%